Healthcare utilization and costs associated with tyrosine kinase inhibitor switching in patients with chronic myeloid leukemia. Issue 4 (2nd April 2016) - Kropf, Patricia; Barnes, Gisoo; Tang, Boxiong; Pathak, Ashutosh; Issa, Jean-Pierre J.
Abstract: Differences in healthcare utilization and costs were examined in chronic myeloid leukemia (CML) patients experiencing first-, second- and third-line tyrosine kinase inhibitor (TKI) therapy. Three CML cohorts were identified from the Truven Health MarketScan® database: No-Switch Cohort (NSc) = did not switch from first-line; One-Switch Cohort (OSc) = switched from first- to second-line only; Two-Switch Cohort (TSc) = switched to second- and then third-line. A total of 3510 patients were identified (mean = 54%; age = 55.8 years). NSc comprised 81% of the sample, OSc comprised 15% and 4% were in the TSc. First-line utilization/costs were significantly higher in the OSc/TSc compared to the NSc. Second-line hospital/outpatient visits and costs were higher in TSc compared to OSc. TSc experienced a significant cost increase from first- to second-line ($4226.46), twice that of OSc ($2488.03). TKI switching is associated with a substantial increase in healthcare utilization and costs, particularly for patients who switch twice.